ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN INTERNET CORPORATE REPORTING - Fikrisani, Muchammad; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the factors that influence the level of internet corporate reporting disclosure on manufacturing companies listed on Bursa Efek Indonesia (BEI) in 2013. Variables used in this study are company size, public ownership, company performance, audit size, leverage and additional funds.The method of this study is secondary data analysis towards annual reports of manufacturing  companies  published  in  Bursa  Efek  Indonesia  (BEI) in  2013.  This  study  used purposive  sampling  method  and  multiple  linear  regression model  as  the  analysis  instrument. Before conducting the regression test, it was examined by the classical assumption tests.The result of this study indicates that public ownership, audit size and leverage do not have significant influence with the level of internet corporate reporting disclosure of a company. This study indicates that company size, company performance and additional fund have a significant influence with the level of internet corporate reporting disclosure of a company.